Nurses’ Awareness of Infection Control Measures, and the Role and Effect in Patient and Family Education - Sahar Hammoud; Bassam Ghazi; Mohamad Nassredine; Mohamad Abou Haidar (European Scientific Journal, ESJ, 2017)
Background: Healthcare Associated Infections are serious problems in healthcare sector that threatened patient safety since decades till present. The proper adherence to infection control measures is a major factor in reducing these infections. Objectives: The objectives of this study were, to assess the level of nurses’ awareness with infection control measures in Lebanon and to determine its role in implementing patient and family education. Methodology and Results: A quantitative study was done. Questionnaires were distributed over 260 nurses, and 260 patients and family members at four well known hospitals in Lebanon. The study showed a high level of infection control awareness (81.57 %) among Lebanese nurses, and showed that Lebanese hospitals are training their nurses on IC topics (99.1 % of nurses were trained). As for patients and family members’ education, the JCI accredited hospital showed the highest level of education on infection control measures (58.3 %). Conclusion and Recommendations: The study showed that nurses who had a high awareness in infection control educated more their patients and family members on these measures than nurses with low awareness. (64.1 % and 42.1 % when educating on respiratory hygiene, p=0.013, 86.2 % and 57.9 % when educating on usage of PPE, p=0.000, 89.2 % and 68.4 % when educating on the reason for isolation, p=0.001). The major recommendations were to enhance the culture that believes in the partnership between patients, their families and healthcare providers at the hospitals level, and to include a new standard in the Lebanese Accreditation Standards that requires educating patients and family members on infection control measures at the Ministry of Public Health level.